Review of Maleic–Itaconic Acid Copolymer Purported as Urease Inhibitor and Phosphorus Enhancer in Soils. (1st March 2014) - Chien, S. H.; Edmeades, D.; McBride, R.; Sahrawat, K. L.
Abstract : The fertilizer additive products Nutrisphere and Avail use a coating of maleic–itaconic acid copolymer and have been marketed worldwide. It is claimed that the copolymer (trade name: Nutrisphere) enhances the efficiency of urea‐N use by inhibiting urea hydrolysis and reducing ammonia (NH3 ) volatilization from urea. It is also claimed that the same copolymer (trade name: Avail) prevents or reduces the conversion of soluble P fertilizer to less soluble forms in the soil and thus enhances the efficiency of fertilizer P. Consequently, it is claimed that both additive products can increase crop yields by 10 to 15%. This review critically examines these claims by considering the basic polymer and soil chemistry, and agronomic effectiveness of these products in the field. It is found that the copolymer does not retard urea hydrolysis and the subsequent NH3 volatilization. Theoretical calculations found that the amount of copolymer recommended for commercial use (0.25% of P fertilizers) is too small to have any significant effect on soil P chemistry. These results are consistent with evidence derived from field trials, which show that these products have very little practical effect on crop production. Accordingly, it is recommended that these products not be promoted to farmers as a means to either increase efficiency of fertilizer urea‐N and fertilizer P or to enhance crop production.